2001
DOI: 10.2337/diacare.24.3.472
|View full text |Cite
|
Sign up to set email alerts
|

Role of Common Sequence Variants in Insulin Secretion in Familial Type 2 Diabetic Kindreds

Abstract: OBJECTIVE -We have demonstrated high heritability of insulin secretion measured as acute insulin response to glucose times insulin sensitivity (disposition index). Furthermore, we showed that obese normoglycemic family members of a type 2 diabetic proband failed to compensate for the insulin resistance of obesity by increasing insulin secretion. In this study, we tested the primary hypotheses that previously described variants in the pancreatic sulfonylurea receptor gene (SUR1 or ABCC8), glucokinase (GCK) gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…However, the GCK G(Ϫ30)A association is also supported by a number of other previous reports of diabetes/diabetes-related traits for this allele (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and thus may be considered less likely to be a false positive than an SNP without such evidence.…”
Section: Variants In the Six Known Mody Genessupporting
confidence: 52%
See 1 more Smart Citation
“…However, the GCK G(Ϫ30)A association is also supported by a number of other previous reports of diabetes/diabetes-related traits for this allele (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and thus may be considered less likely to be a false positive than an SNP without such evidence.…”
Section: Variants In the Six Known Mody Genessupporting
confidence: 52%
“…The G(Ϫ30)A variant upstream from the GCK promoter has been inconsistently associated with diabetes, but it has frequently been found to be associated with increased fasting glucose (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). There have also been several published nominal associations for variants in IPF1 with the common form of type 2 diabetes (34 -37).…”
mentioning
confidence: 99%
“…Analysis of subjects who had undergone frequently sampled intravenous glucose tolerance tests was done using mixed effects linear regression analysis in SPSS v 10.1 (SPSS, Chicago, Ill., USA) [34]. Family membership was a random factor, genotype and diagnosis (normal and IGT) were fixed factors, and age and ln-transformed BMI were covariates, as we have described previously [35]. BMI, insulin sensitivity index (S I ), acute insulin response to glucose (AIR g ), and disposition index (S I *AIR g ) [36] were all ln-transformed prior to analysis.…”
Section: Methodsmentioning
confidence: 99%
“…These associations may be partly due to the impact of this polymorphism on insulin sensitivity, as an association with high insulin resistance has been reported for the -30G>A allele 15 . However, this is not a universal finding since Elbein et al found no significant influence of this polymorphism on the insulin sensitivity index 20 . In the present study on Iranian subjects, an association between this polymorphism and BMI was not found.…”
Section: Discussionmentioning
confidence: 69%
“…However, these findings are challenged by those of other studies 12,24,[30][31][32] and so are not consistent. Furthermore, previous studies have failed to find any significant effect of this polymorphism on insulin secretion 20,24 . Nevertheless, Rose et al 15 found that the -30G>A allele is associated with high FPG and Post-Oral Glucose Tolerance Test (OGTT) glycemia, as well as impaired glucose regulation and other features of WHO-defined metabolic syndrome 15 .…”
Section: Allelesmentioning
confidence: 95%